Hurry and the monarch - O'Flatharta, Antoine; So, Meilo (New York : Knopf : Distributed by Random House, 2005)
Hurry the tortoise befriends a monarch butterfly when she stops in his garden in Wichita Falls, Texas, during her migration from Canada to Mexico. Includes facts about monarch butterflies.
Accelerated Reader/Renaissance Learning
A Junior Library Guild selection.
85978
Keywords: Turtles -- Fiction; Monarch butterfly -- Fiction; Butterflies -- Fiction; Turtles -- Juvenile fiction; Monarch butterfly -- Juvenile fiction; Butterflies -- Juvenile fiction; Wichita Falls (Tex.) -- Fiction; Wichita Falls (Tex.) -- Juvenile fiction